What the Pandemic Revealed: The Importance (and Fragility) of Mental Health and Solidarity (Revista Iberoamericana de Bioética, 2023)
The pandemic and its impact on mental life and social relations have not yet been fully established. However, there is no doubt that it has been a unique period that will leave traces, questions and lessons learned. Two themes in particular emerged: on one hand, the importance—and fragility—of mental health and on the other hand, solidarity, a value that was invoked to respect coexistence and to follow the rules applied and measures taken in health matters; and also, to support the limitations and impositions that followed. Solidarity was promoted to uphold the importance of the common good over individual interests. The structure of the two themes—the so-called mental health and solidarity—is a pretext to reflect on the dynamics of the human being brought to the fore during this significantly adverse and unfavorable period.
Keywords: pandemic; mental health; solidarity; mental life; social relations